Heat treatment effect study on bioactive compounds of unconventional food plants (Research, Society and Development, 2020)
This study aimed to evaluate the effect of heat treatment (HT) on bioactive and antinutritional compounds of different PANC (Cnidoscolus aconitifolius (chaya), Tallinum paniculatum   (jewels of opar), Urtica dioica L. (nettle leaf), Costus spicatus (spiked spiralflag ginger), Portulaca oleracea (purslane), Mentha suaveolens (pineapple mint) and  Sonchus oleraceus (sow thistle). The concentrations of the bioactive compounds such as total phenolics (TF) and flavonoids, antinutritionals (tannins and oxalates) and antioxidant activity (AA) were carried out according to the Analytical Standards of the Adolfo Lutz Institute. The compounds contents (mg/100g) in PANC before the HT ranged as follows: bioactive compounds (TF from 2.04±0.04 to 37.40±0.46, flavonoids from 145.96±0.61 to 410.73±1.93), anti-nutritional compounds (tannins from 4.47±0.46 to 211.74±2.96 and oxalates from 2.61±0.13 to 4.41±0.22), AA (IC50) from 2.13±0.05 to 7.05±1.36. The HT applied to the samples provided an increase of compounds concentration percentage in most PANC, which ranged from: 38.13 to 99.84% (TF); 1.2 to 37% (flavonoids); 21.21 to 116.55% (tannins); 45.92 to 77.63 (oxalates), as well as in AA, which ranged from 14.5 to 67%. On the other hand, there was a reduction of compounds concentration percentage in other PANC from: 45 to 73% (TF); 8 to 29% (flavonoids); 15 to 74% (tannins); 5.36 to 27.44% (oxalates) and 44.49 to 79.84% (AA). It is concluded that, in general, the applied HT favored an increase in the concentration of bioactive compounds and AA in PANC, the same not happening for antinutricional activity. It is generally concluded that HT favored an increase of bioactive compounds and AA concentration in PANC, however the same did not occur for antinutritional activity.